National survey of Ebola-related knowledge, attitudes and practices before the outbreak peak in Sierra Leone: August 2014 - Mohamed F. Jalloh; Paul Sengeh; Roeland Monasch; Mohammad B. Jalloh; Nickolas DeLuca; Meredith Dyson; Sheku Golfa; Yukiko Sakurai; Lansana Conteh; Samuel Sesay; Vance Brown; Wenshu Li; et al. (2017)
The 2014-2015 Ebola epidemic in West Africa was the largest ever to occur. In the early phases, little was known about public knowledge, attitudes and practices (KAP) relating to Ebola virus disease (Ebola). Data were needed to develop evidence-driven strategies to address gaps in knowledge and practice.